Long-term outcomes of transoral incisionless fundoplication for gastro-esophageal reflux disease: systematic-review and meta-analysis - Testoni, Sabrina; Hassan, Cesare; Mazzoleni, Giorgia; Antonelli, Giulio; Fanti, Lorella; Passaretti, Sandro; Correale, Loredana; Cavestro, Giulia Martina; Testoni, Pier Alberto (Endoscopy International Open, 2021)
Background and study aims Few reports exist about long-term outcomes of transoral incisionless fundoplication (TIF) for treating refractory gastro-esophageal reflux disease (GERD). Methods A literature search of four major scientific databases was performed up to May 2020 for studies reporting on more than 3-year outcomes of TIF. Data on atient satisfaction, proton pump inhibitor (PPI) daily consumption, PPI use reduction, GERD health-related quality-of-life (GERD-HRQL) score, and normalization of heartburn and regurgitation scores were pooled and summarized with forest plots. Publication bias and heterogeneity were explored.Results Overall, eight studies (418 patients, 232 men; 55.5 %) with a mean follow-up of 5.3 years (range: 3–10 years) were included. The pooled proportion of patient-reported satisfaction before and after TIF was 12.3 % (95 % CI:12.3–35.1 %, I2 = 87.4 %) and 70.6 % (95 % CI:51.2–84.6, I2 = 80 %), respectively, corresponding to an odds ratio of 21.4 (95 % CI:3.27–140.5). Pooled rates of patients completely off PPIs and on occasional PPIs were 53.8 % (95 %CI: 42.0 %-65.1 %) and 75.8 % (95 %CI: 67.6–82.6), respectively. The pooled estimated mean GERD-HRQL scores off PPI before and after TIF werey 26.1 (95 %CI: 21.5–30.7; range: 20.0–35.5) and 5.9, respectively (95 %CI:0.35.1–11.4; range: 5.3–9.8; P < 0.001). The overall pooled rates of heartburn and regurgitation scores normalization were 73.0 % (95 %CI: 0.62–0.82) and 86 %, respectively (95 %CI: 75.0–91.0 %). Conclusion Our study shows that TIF appears to offer a long-term safe therapeutic option for selected patients with GERD who refuse life-long medical therapy or surgery, are intolerant to PPIs, or are at increased surgical risk.